Rescue left bundle branch area pacing in coronary venous lead failure or nonresponse to biventricular pacing: Results from International LBBAP Collaborative Study Group - Vijayaraman, Pugazhendhi; Herweg, Bengt; Verma, Atul; Sharma, Parikshit S; Batul, Syeda Atiqa; Ponnusamy, Shunmuga Sundaram; Schaller, Robert D; Cano, Oscar; Molina-Lerma, Manuel; Curila, Karol; Huybrechts, Wim; Wilson, David R; et al. (Heart rhythm, 2022)
BACKGROUND: Cardiac resynchronization therapy (CRT) using biventricular pacing (BVP) is effective in patients with heart failure, left bundle branch block (LBBB), and reduced left ventricular function. Left bundle branch area pacing (LBBAP) has been reported as an alternative option for CRT. OBJECTIVE: The purpose of this study was to assess the feasibility and outcomes of LBBAP in patients who failed conventional BVP because of coronary venous (CV) lead complications or who were nonresponders to BVP. METHODS: At 16 international centers, LBBAP was attempted in patients with conventional CRT indication who failed BVP because of CV lead complications or lack of therapeutic response to BVP. Heart failure hospitalization (HFH) and death, echocardiographic outcomes, procedural data, pacing parameters, and lead complications including CV lead failure are reported. RESULTS: LBBAP was successfully performed in 200 patients (CV lead failures 156; nonresponders 44) (age 68 ± 11 years; female 35%; LBBB 55%; right ventricular pacing 23%; ischemic cardiomyopathy 28%; nonischemic cardiomyopathy 63%; left ventricular ejection fraction [LVEF] ≤35% in 80%). Procedural duration was 119.5 ± 59.6 minutes, and fluoroscopy duration was 25.7 ± 18.5 minutes. LBBAP threshold and R-wave amplitudes were 0.68 ± 0.35 V @ 0.45 ms and 10.4 ± 5 mV at implant, respectively, and remained stable during mean follow-up of 12 ± 10.1 months. LBBAP resulted in significant QRS narrowing from 170 ± 28 ms to 139 ± 25 ms (P <.001) with V6 R-wave peak times of 85 ± 17 ms. LVEF improved from 29% ± 10% at baseline to 40% ± 12% (P <.001) during follow-up. The risk of death or HFH was lower in those with CV lead failure than in nonresponders (hazard ratio 0.357; 95% confidence interval 0.168-0.756; P = .007) CONCLUSION: LBBAP is a viable alternative to CRT in patients who failed conventional BVP due to CV lead failure or who were nonresponders.
Keywords: Stroke Volume; Bundle-Branch Block; Female; výsledek terapie; ženské pohlaví; Heart Failure; Nonresponder; funkce levé komory srdeční; Cardiac Resynchronization Therapy; lidé; srdeční selhání; Treatment Outcome; Left bundle branch area pacing; Arrhythmias, Cardiac; Electrocardiography; Cardiac resynchronization therapy; elektrokardiografie; srdeční resynchronizační terapie; Cardiac Pacing, Artificial; Hisův svazek; Biventricular pacing failure; Aged; tepový objem; Heart failure; blokáda Tawarova raménka; Bundle of His; lidé středního věku; senioři; kardiostimulace umělá; Middle Aged; srdeční arytmie; Ventricular Function, Left; Humans